An Efficient approach Network Selection and Fast Delivery Handover Route 5G LTE Network - Mishra, Om Prakash; Morghare, Gaurav (2019 3rd International Conference on Trends in Electronics and Informatics (ICOEI), 2019)
To move from 4G to 5G technology spectrum deficiency is an important criteria which can be overcome by an efficient technology called Cognitive Radio (CR). This can be achieved by continuous sensing the spectrum band, and detecting the unused frequency bands which would be not used by licensed band and without any unwanted interference to the primary user or licensed user (PU). We Proposed NN-PSO method for network selection and Fast Delivery handover route mechanism in order to increase system efficiency by consider more number of SUs in network and providing to their preferences, and respect the criteria of primary network operators, at the same time. The goal is to provide SUs good network and fast delivery handover route with a high QoS based on the criteria of SU, subject to the interference boundation of each existing network with other channels. The proposed technique Neural Network and Particle swarm optimization would be use to solve the Network selection and optimization problem. Finally, experimental results and numerical parameters represent the effectiveness of the proposed NN-PSO methods to finding a near-optimal solution for network selection.